A green solid-phase method for preparation of carbon nitride quantum dots and their applications in chemiluminescent dopamine sensing1. Issue 68 (25th July 2015) - Fan, Xiaoqing; Feng, Yang; Su, Yingying; Zhang, Lichun; Lv, Yi
<x xml:space="preserve">Abstract</x> Schematic illustration for the preparation of g-CNQDs though a thermal condensation process and CL of the g-CNQDs–K3[Fe(CN)6] system.